Family Instability and Exposure to Violence in the Early Life Course. (11th October 2017) - Cavanagh, Shannon E.; Stritzel, Haley; Smith, Chelsea; Crosnoe, Robert
Abstract : Family instability has been linked with a host of outcomes across the early life course. This study extends this literature by connecting instability with violence in the community by examining the associations among family structure, family structure change, and secondary exposure to violence during adolescence across diverse segments of the population. Using longitudinal data from the Project on Human Development in Chicago Neighborhoods study, we found that living with a single parent and experiencing family structure changes were associated with secondary exposure to violence. Multiple group models suggest that partner change translated into more exposure for boys than girls. Findings also suggest that family instability may lead to more secondary exposure to violence for African American youth.